CAHOST: An Excel Workbook for Facilitating the Johnson-Neyman Technique for Two-Way Interactions in Multiple Regression - Carden, Stephen W.; Holtzman, Nicholas S.; Strube, Michael J (Frontiers in Psychology, 2017)
When using multiple regression, researchers frequently wish to explore how the relationship between two variables is moderated by another variable; this is termed an interaction. Historically, two approaches have been used to probe interactions: the pick-a-point approach and the Johnson-Neyman technique. The pick-a-point approach has limitations that can be avoided using the Johnson-Neyman technique. Currently, the software available for implementing the Johnson-Neyman technique and creating corresponding figures lacks several desirable features--most notably, ease of use and figure quality. To fill this gap in the literature, we offer a free Microsoft Excel 2013 workbook, CAHOST (a concatenation of the first two letters of the authors' last names), that allows the user to seamlessly create publication-ready figures of the results of the Johnson-Neyman technique.